Рlanning independent study of master’s degree students in the process of teaching foreign languages - Stativka, O. (Problems of Engineer-Pedagogical Education, 2021)
The article emphasizes the important role of foreign language training of master’s degree students at higher education institutions according to the requirements of modern society for the training level of a future specialist. Foreign language skills are considered to be one of the main cultural competencies of a master's degree graduate; the author stresses that a new understanding of the objectives of foreign language teaching is related to the key provisions in the modern educational paradigm, such as ensuring continuity in education, prioritizing independent work, self-control and self-estimation, readiness to work with modern sources of information, orienting teaching around the development of communication skills and abilities. The concept of students’ independent work has been considered, the goals of independent study of master’s degree students while teaching them a foreign language course have been defined (systematization and reinforcement of students’ theoretical knowledge and practical skills, promotion of critical analysis and assessment of modern scientific achievements, generation of new ideas to support the required research and analysis; implementation of research activities using modern instruction tools, teaching methods, information and communication technologies; development of the competencies and skills necessary to analyze the results of scientific research and apply them to solve specific research problems, skill-building necessary for self-development, selfimprovement and self-realization). The work highlights the features and forms of planning the independent work of MA students in the process of foreign languages training (thoroughly analyzing the training material, working with authentic information sources, building a terminological vocabulary, preparing written works (abstracts, conference papers, articles), annotating and abstracting texts for specific purposes, preparing a report and presentation at a conference in a foreign language). The article concludes that the effective planning of the independent study of MA students at a higher education institution can help not only optimize its individual types, but also create conditions for increasing the engagement, independence and responsibility of MA students, both in the classroom and outside. The intensification of the independent study of MA students provides for the application of educational technologies appropriate to their level with the aim of solving the task of developing a scientific thinking style, study skills and creative activity. Individualization of the independent study of MA students promotes better educational attainment, setting the stage for independent choice, self-determination and self-realization of students.